Technology Utilization, Work Experience, and Gender as Predictors of School Counselors’ Ability in Conducting Needs Assessment - Farikha Wahyu Lestari; Arri Handayani; Latif Anshori Kurniawan; Farikha Wahyu Lestari; Arri Handayani (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Needs assessment is a fundamental component of guidance and counseling services because it provides the basis for developing data-driven programs that are responsive to students’ actual needs. However, guidance and counseling (GC) teachers’ competence in conducting needs assessments may vary according to individual and professional characteristics, particularly technology utilization. This study aimed to analyze GC teachers’ competence in conducting needs assessments and examine differences in competence based on gender, years of professional experience, and technology utilization. A quantitative approach with a descriptive-analytical survey design was employed. The participants consisted of 90 GC teachers selected through simple random sampling. Data were collected using a structured questionnaire and analyzed through descriptive statistics, independent-samples t-tests, and one-way analysis of variance (ANOVA). The findings revealed that GC teachers’ needs assessment competence was generally at a moderate-to-good level (M = 47.11, SD = 17.04). The results further indicated that there were no statistically significant differences in needs assessment competence based on gender (p = .995) or years of professional experience (p = .857). In contrast, technology utilization showed a statistically significant relationship with needs assessment competence (F = 18.178, p < .001), with teachers demonstrating higher levels of technology utilization exhibiting substantially greater competence in conducting needs assessments. These findings suggest that technological competence plays a more important role in enhancing needs assessment competence than demographic characteristics. Therefore, strengthening digital literacy and technology-based assessment skills should be prioritized within professional development programs, counseling supervision, and educational quality improvement initiatives to support the implementation of effective data-driven guidance and counseling services in the digital era.